Analysis of Variables Affecting the Performance Quality of Contractors in the Execution of Fast-Drying Concrete Pouring on the Maintenance of the Jakarta Outer Ring Road Toll, Sections W2S, S, and E - Agung Helisasongko; Mawardi Amin; Muhammad Isradi (Green Publisher Indonesia, 2026)
Toll road maintenance requires effective and efficient strategies to ensure that repair work can be completed quickly without reducing construction quality, particularly in projects using rapid-setting concrete. This study aims to analyze the variables affecting contractor quality performance in the implementation of fast-drying concrete pouring on the maintenance of the Jakarta Outer Ring Road (JORR) sections W2S, S, and E, as well as to identify the most dominant factors influencing project quality. The study employed a quantitative approach using Structural Equation Modeling-Partial Least Squares (SEM-PLS) combined with Importance Performance Map Analysis (IPMA). Data were collected through questionnaires distributed to 96 respondents consisting of project owners, contractors, supervising consultants, and rapid-setting concrete producers. The results revealed that material management, work motivation, work equipment, and work environment significantly influenced project quality performance. Material was identified as the most dominant factor with the highest total effect value, while communication significantly affected work motivation as a mediating variable. The model explained 67.9% of the variance in project quality performance. In conclusion, improving material management, strengthening work motivation, optimizing equipment readiness, and creating a supportive work environment are essential strategies for enhancing the quality of fast-drying concrete maintenance projects on toll roads.